ANALISIS SISTEM PENGUKURAN KINERJA DRUCKEN PHOTO BOOTH DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD - Jasmine Shafa Khairunnisa (2021)
The development of the creative industry has increased significantly in this digitalization era. The creative industry, especially Photo Booth, is an example of a photography sector, one of which is Drucken Photo Booth. The purpose of this study was to measure the performance of Drucken Photo Booth using the Balanced Scorecard approach. By measuring performance with the Balanced Scorecard approach, you can find out the actual number of Drucken Photo Booth's performance by knowing the strategy mapping with the Strategy Map and then weighting its priorities with the Analytical Hierarchy Process and weighting its performance with Key Performance Indicators which later, when weighted, can be given suggestions for improvements to become lessons and evaluations for Drucken Photo Booth. The results of this study indicate that the highest priority of this company is on the customer perspective which has a priority weight of 0.3989, followed by a financial perspective with a weight of 0.3572, then an internal business perspective of 0.1607, and the lowest priority value falls on a growth and learning perspective with a value of 0.0832. Meanwhile, the performance of Drucken Photo Booth from the financial perspective is 0.0645, the customer perspective is 0.2525, the internal business perspective is 0.1467, and the growth and learning perspective is 0.0287.